The effect of conducted electrical weapons on the human body - Laima, Sigitas; Fomin, Dmitrij; Jasulaitis, Algimantas; Andriuškevičiūtė, Gerda; Chmieliauskas, Sigitas; Sabaliauskas, Vaidas; Sergejevas, Vladimiras (Acta medica Lituanica, 2014)
Background and objective. Fatal accidents occur due to the effect of electric current on the human body. The most common reasons are invalid electrical installations or misuse of electrical devices, but rarely murder and suicide cases are possible. Recently, conducted electrical weapon handling cases which resulted in sudden death have been observed. In this article we have provided our findings about the effects of conducted electrical weapons on the heart muscle, with emphasis on the use of conducted electrical weapons by officials. Materials and methods. Lithuanian and foreign authors’ findings about the effect of conducted electrical weapons on the heart muscle are analysed. Recommendations for the use of these weapons are made to the officials. The results are evaluated using descriptive statistical methods. Results. The working principle of this weapon is the effect on striated muscles. The muscles contract reacting to electric impulses, hence the affected person cannot struggle with the policeman. Although this weapon was created as a safe tool to suppress aggressive persons, new researches revealed its dangerous effect on the heart muscle that caused fatal arrhythmias. Conclusions. Stress on the body, systemic disease and the presence of chemicals in the body modify the body’s response to electrical impulses that directly increase the risk of cardiac arrhythmia due to the developing of ventricular fibrillation and probability of sudden cardiac death. It is recommended to officials who use conducted electrical weapons that in the location of the event there should be qualified medical personnel (ambulance) able to provide the first aid in case of complications after the use of the weapon.